Nitrogen Application for Spring Growth of Cool‐season Grasses Overseeded in Unimproved Warm‐season Pasture. Issue 1 (26th June 2015) - Bartholomew, P. W.
Abstract : In the southern Great Plains fall overseeding of annual forages into dormant warm‐season pasture can increase herbage production in spring and early summer of the following year, but production in early spring, when it is most needed, is usually limited and competition between cool‐ and warm‐season components of mixed pasture may result in only small benefit in total annual yield. The effects of early‐producing species, or of stimulation of early growth by nitrogen (N) fertilizer application to the cool‐season crop, on early‐season availability of herbage and on competition within mixed pasture were evaluated in a series of experiments. Rye ( Secale cereale L.), oats ( Avena sativa L.), or annual ryegrass ( Lolium multiflorum Lam.) were overseeded into dormant unimproved warm‐season pasture in fall and provided 22, 45, or 67 lb/acre of N fertilizer in mid‐February of the following year. Neither rye nor annual ryegrass showed significant advance in early‐season growth (up to early April) resulting from increased N application, and herbage dry matter (DM) yield response was <4.0 lb DM/lb N applied over this period. Over uninterrupted spring growth to a mid‐May harvest, DM yield responses to applied N were similar in rye and annual ryegrass and ranged from 9.3 to 32.3 lb DM/lb N. Oats did not tolerate low winter temperatures. Choice of cool‐season annual grass species for overseeding and level of N application in spring had little impact on DM yield of the warm‐season grass component of mixed cool‐ and warm‐season pasture.